The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s44177-022-00014-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Socio-technical Constraints of Marine Fishers in the Utilisation of Marine Fishery Advisories in Southern Odisha, India

Abstract: Sustainable marine fishing practices are often hindered by local-level factors in areas with high fishery potentials, such as Odisha, India. Scientific services to fishing, such as Marine Fishery Advisories (MFAs) on the Potential Fishing Zone (PFZ) and weather information in the form of Ocean State Forecast (OSF) advisories provided by INCOIS, India, are valuable knowledge products which can help the fishers to overcome several socio-technical constraints (STCs) to effective fishing practices. The present inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…However, local respondents stressed that the nearby village settlements were comparatively less affected by the super cyclone in 1999 because of the dense protective cover of mangroves close to the coastline. During the survey, it was clear that there was low uncertainty in responses about the high impact of extreme climate events on the degradation of mangroves in the region (Figure 3a,b), corroborating earlier reports from Odisha (Sanathanam and Kundu, [30]; at Talasari). It has been well established that the especially rich mangroves of Odisha in the Kendrapara district have acted as a shield to reduce the intensity and impact of cyclones and tsunamis.…”
Section: Sea Level Rise and Extreme Climate Eventssupporting
confidence: 88%
See 3 more Smart Citations
“…However, local respondents stressed that the nearby village settlements were comparatively less affected by the super cyclone in 1999 because of the dense protective cover of mangroves close to the coastline. During the survey, it was clear that there was low uncertainty in responses about the high impact of extreme climate events on the degradation of mangroves in the region (Figure 3a,b), corroborating earlier reports from Odisha (Sanathanam and Kundu, [30]; at Talasari). It has been well established that the especially rich mangroves of Odisha in the Kendrapara district have acted as a shield to reduce the intensity and impact of cyclones and tsunamis.…”
Section: Sea Level Rise and Extreme Climate Eventssupporting
confidence: 88%
“…Respondents agreed, with low to medium uncertainty, that local people are directly as well as indirectly dependent on the mangrove forests, and that local socio-economics have a high to very high impact on mangroves (Figure 3a,b). The eco-sensitivity of the area has deterred domination of marine fishing activities in general, and there was a cessation during the fishing ban periods [30]. Respondents indicated that local poverty and socio-economic factors have significantly affected the mangroves' health in the region, and that agriculture expansion, along with the pressure of fuelwood, is tremendous.…”
Section: Local Socio-economicsmentioning
confidence: 99%
See 2 more Smart Citations